2019
DOI: 10.1038/s41598-019-44404-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cell cluster phenotype allows monitoring response to treatment and predicts survival

Abstract: Circulating tumor cells (CTCs) are putative markers of tumor prognosis and may serve to evaluate patient’s response to chemotherapy. CTCs are often detected as single cells but infrequently as clusters and are indicative of worse prognosis. In this study, we developed a short-term culture of nucleated blood cells which was applied to blood samples from breast, lung, esophageal and bladder cancer patients. Clusters of different degrees of compactness, classified as very tight, tight and loose were observed acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 38 publications
1
50
0
Order By: Relevance
“…A few studies, including ours, have reported that the presence of CTC clusters ( ≥ 1 cluster) was pejorative for patient survival for breast, pancreatic, prostate, colon, and lung cancers [30,40,[43][44][45] without signs of metastatic disease at the time of analysis. In connection with these observations, a recent study focused on the prognostic value of in vitro breast and lung cancer CTCs cluster formation [46]. CTCs isolated from blood samples at baseline and during chemotherapy were cultured, and a correlation between CTC cluster phenotype and both therapeutic response and overall survival was found.…”
Section: Prognostic Valuementioning
confidence: 99%
“…A few studies, including ours, have reported that the presence of CTC clusters ( ≥ 1 cluster) was pejorative for patient survival for breast, pancreatic, prostate, colon, and lung cancers [30,40,[43][44][45] without signs of metastatic disease at the time of analysis. In connection with these observations, a recent study focused on the prognostic value of in vitro breast and lung cancer CTCs cluster formation [46]. CTCs isolated from blood samples at baseline and during chemotherapy were cultured, and a correlation between CTC cluster phenotype and both therapeutic response and overall survival was found.…”
Section: Prognostic Valuementioning
confidence: 99%
“…They also found that patients who were sensitive and resistant to chemotherapy exhibited loose and tight clusters, respectively. Moreover, tight clusters were clearly correlated with poor patient survival [167]. Conversely, in early-stage lung cancer, patients with CTC clusters exhibit significantly lower recurrence-free survival and OS than patients with single CTCs or undetectable CTCs [168].…”
Section: How Ctcs Improve Metastasis Prediction and Diagnosis?mentioning
confidence: 93%
“…Beyond the genetic assessments (e.g., trunk versus branch alterations) enabled through these approaches, the presence of CTCs in both early and late metastatic stage disease corresponds with worse patient outcomes and decreased survival rates [158,159]. Even more relevant to therapeutic targeting, decreases in CTCs following treatment are associated with a better overall survival, and, thus, quantitative changes in CTCs are now being employed as markers of early treatment response [160]. Perhaps most importantly, various genetic assessments, including single cell DNA sequencing, copy number alterations, and the myriad of CIN-based analyses may provide additional and critical clinical information.…”
Section: The Impact Of Cin On Therapeutic Targetingmentioning
confidence: 99%
“…Perhaps most importantly, various genetic assessments, including single cell DNA sequencing, copy number alterations, and the myriad of CIN-based analyses may provide additional and critical clinical information. For example, CTCs isolated from liquid biopsies are more readily amenable to sequential sampling than traditional tumor biopsies, and they can provide 'real-time' insight into tumor genetics, CIN, and intratumoral heterogeneity that may prove useful in monitoring disease progression, treatment responses [160], and/or modifying treatment decisions [147]. .…”
Section: The Impact Of Cin On Therapeutic Targetingmentioning
confidence: 99%